The Utilization of Kepyar Castor Oil (Ricinus Communis) and Alumina Silica Catalyst in Alcoholysis Process - Kiagus Ahmad Roni; Netty Herawati; Dian Kharisma Dewi; Sri Martini (Journal of Engineering and Scientific Research, 2021)
Castor oil is one of the vegetable oils that has not been used optimally. In the manufacture of biodiesel, vegetable oil is needed as a raw material. By using an aluminum silica catalyst which is a waste from the petroleum cracking process at PT. Pertamina RU III Palembang. This research aims to prove that the raw material for vegetable oil in the form of castor oil can be used as raw material for making biodiesel with the help of waste catalyst from the cracking process of Pertamina Unit III Palembang as a catalyst process and with the alcoholysis method. Based on the research that has been done, it can be concluded that castor oil can be used as raw material for making biodiesel using heterogeneous catalysts which are used as catalysts for fracturing crude oil at PT. Pertamina RU III, and with operating conditions of temperature 383oK, stirring speed of 300 rpm, ratio of oil and ethanol 5 mgek/mgek, and reaction time of 60 minutes. With the above operating conditions, the biodiesel conversion from the alcoholysis process was obtained at 94.08%. So that further research can be developed on the manufacture of biodiesel with castrol oil as raw material with the help of a catalyst reaction from cracked crude oil from PT Pertamina RU III Palembang.